Amnesia Suffered by Leticia Ortiz in Chris Morgan’s the Fast Saga Films - Naima Ulinda; Firdiansyah Firdiansyah; Al Amin (The Future of Education Journal, 2026)
This study examines the portrayal of amnesia experienced by Leticia Ortiz in Fast & Furious (2009), Fast & Furious 6 (2013), and Furious 7 (2015) by applying a psychological approach. The research addresses two main questions: (1) what are the causes of Leticia Ortiz’s amnesia in The Fast Saga?; and (2) what kind of treatment is applied to cure Leticia Ortiz in the film of Fast Saga? Employing a qualitative descriptive method using documentation techniques, with dialogues and scenes from the selected films serving as the primary data. The analysis is based on Hilgard’s psychological framework and Jenny Mackay’s theory of amnesia to interpret the character’s memory disorder and recovery process. The findings reveal that Leticia’s amnesia is represented through two principal causes, namely sudden strike on memory and a shocking condition. Furthermore, the films depict two major approaches to managing her condition, consisting of living with amnesia and hoping for a cure. The research concludes that The Fast Saga presents amnesia not merely as a medical condition but also as a psychological experience that influences identity, emotional adaptation, and interpersonal relationships. Through Leticia Ortiz’s character, the films illustrate that memory loss functions as both a psychological phenomenon and a narrative strategy that shapes character development and emotional conflict.